2013
DOI: 10.1042/bj20131080
|View full text |Cite
|
Sign up to set email alerts
|

The calmodulin-like protein CML43 functions as a salicylic-acid-inducible root-specific Ca2+ sensor in Arabidopsis

Abstract: Many signalling pathways in plants are regulated by the second messenger calcium (Ca(2+)). In the standard model, Ca(2+)-sensor proteins, such as CaM (calmodulin), detect Ca(2+) signals and subsequently regulate downstream targets to advance the signal transduction cascade. In addition to CaM, plants possess many CMLs (CaM-like proteins) that are predicted to function as Ca(2+) sensors, but which remain largely uncharacterized. In the present study, we examined the biochemical properties, subcellular localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 59 publications
7
37
0
1
Order By: Relevance
“…The expression of CML43 is up-regulated when Arabidopsis plant is treated with SA. Thus, CML43 functions as a SA-inducible, rootspecific Ca 2þ sensor in Arabidopsis (Bender et al, 2014). We found that SA enhanced the expression of four genes within 4 h under Al stress, indicating that SA can regulate gene expression to generate physiological responses for Al tolerance in soybean through Ca 2þ signaling pathway.…”
Section: Sa Affects the Levels Of Ca 2þ In Ca 2þ Content And Expressimentioning
confidence: 89%
See 1 more Smart Citation
“…The expression of CML43 is up-regulated when Arabidopsis plant is treated with SA. Thus, CML43 functions as a SA-inducible, rootspecific Ca 2þ sensor in Arabidopsis (Bender et al, 2014). We found that SA enhanced the expression of four genes within 4 h under Al stress, indicating that SA can regulate gene expression to generate physiological responses for Al tolerance in soybean through Ca 2þ signaling pathway.…”
Section: Sa Affects the Levels Of Ca 2þ In Ca 2þ Content And Expressimentioning
confidence: 89%
“…During an intracellular Ca 2þ signal transduction, Ca 2þ is bound to calcium-binding proteins. Ca 2þ signals can be detected by Ca 2þ sensor proteins, such as calmodulin (CaM) or CaM-like proteins (CMLs) (Bender et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When CML sequences were judged as incomplete, the prediction of full protein sequences (file 1 in the supplementary material online) was carried out using EXPASY tools (http://web.expasy.org/translate/) and an ab initio strategy using FGENESH (http:// www.softberry.com) for prediction of the full protein sequence (sequences are provided in file 1 in the supplementary material online). Sequence alignments were performed using Muscle with default parameters (http://www.ebi.ac.uk/ Tools/msa/muscle/) and the phylogenetic trees were generated with the Maximal Likelihood method using MEGA6 (Bootstrap 500) [ root development [29,45]. Groups IV and VI correlate with the emergence of angiosperms and to the formation of new organs, such as seeds and flowers, and this is supported by evidence showing that CML39, a CML from group VI, is essential for seedling establishment in Arabidopsis [30].…”
Section: Cams and Cmls From Green Algae To Angiospermsmentioning
confidence: 99%
“…Some CMLs contain variable N‐ or C‐terminal extensions that could constitute targeting sequences for organelle sorting, or motifs for myristoylation . Growing research on CMLs functional roles has revealed their involvement in different developmental processes, as well as in the response to stresses . This information, together with the presence and diversification of CMLs across plant taxa, allowed speculation that CMLs have distinct functions and that their evolution is related to the necessity for more specialized Ca 2+ sensors in the colonization of new terrestrial environment .…”
Section: Introductionmentioning
confidence: 99%